Educational Transformation in the Digital Era: Big Data Analysis to Increase Teacher Management Efficiency in Vocational High Schools - Sari, Maya Novita; Rahman, Arif; Pisol, Mohd Izzuddin Mohd; Herawati, Endang Sri Budi; Rachmawati, Sela; Aprilia, Triana; Fitriana, Destri (Faculty of Educational Sciences, Universitas Negeri Yogyakarta, 2023)
Big Data analysis has a role in optimizing the efficiency of teacher management in Vocational High Schools during the educational transformation in the digital era. This research uses a literature review method to analyze relevant concepts, theories, and previous research findings. This research emphasizes vocational schools' challenges, such as the rapid evolution of market-driven skills needs and the lack of qualified vocational teachers. This article proposes a systematic data collection and analysis approach to address these challenges, focusing on volume, velocity, and variability in educational big data. Through a